ICHI Ban Unggul Enterprise / Muhammad Afif Firdaus Mohd Ali - Mohd Ali, Muhammad Afif Firdaus (Faculty of Civil Engineering, 2018)
The construction industry has a wide prospect. The activities of construction industries including build a new structure, modification and renovation, also repair and maintenance. The construction industry is also divided into several major segments such as engineer and client. Engineering can be divided by two which is contractor and consultant. Consultant is a group of people consist of engineers and quantity surveyors who evaluate a client's needs and provide expert advice and opinion on what needs to be done. It is the overall planning, co-ordination and control of a project from inception to completion aimed at meeting a client's requirements in order to produce a functional and financially viable project that will be completed on time within authorized cost and to the required quality standards. Contractors is a group of engineers who evaluate the client's needs and actually perform the works. They are the one who agrees (contracts) to work for another usually for a fixed price. They retain control over the work to be done including the means and methods used to do the job, the scheduling of the underlying work, performs the work and determines how the work will get done within the standards and time requirements set. A contractor will generally use his own tools and equipment and may employ others to do the work for them.